UPAYA PENINGKATAN KUALITAS BACAAN AL-QUR’AN SISWA DI LEMBAGA TAHFIZ DAN ILMU AL-QUR’AN - Lulu Hasna Hanifa; Apri Wardana Ritonga; Salsabila Rahmah; Hilma Qurratu Aini (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2023)
This study aims to describe efforts to improve the quality of students' Al-Qur'an reading in Islamic education institutions by knowing the inhibiting factors for increasing the quality of students' Al-Qur'an reading in an institution and determining the method of reading the Qur'an that is suitable for use in many people who study in an Institute. This study used a descriptive research design using library research. Data collection was carried out by classifying reading and analyzing from books, scientific articles and from the Qur'an and taking notes. The results of this study indicate that; first, in reading the Al-Qur'an an appropriate Al-Qur'an learning method is needed so that the originality of the Al-Qur'an is maintained; second, learning the Qur'an in Islamic educational institutions becomes urgent; third, Efforts to improve the quality of Al-Qur'an reading in Islamic educational institutions. The research findings illustrate that the phenomenon of the decline in the quality of students' Al-Qur'an reading can be improved by using the Talaqqi and musyafahah systems in an Islamic educational institution, accompanied by teachers who already have at least one qiraat sanad. This study recommends further research to examine the improvement of the quality of children's Al-Qur'an reading within the family sphere, where the family is the main factor in improving the quality of their children's education.